Political dynasties and poverty: Illustration of measurement and initial evidence of linkages in the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2013)
A political dynasty emerges when an incumbent elected official has at least one relative in elected office in the past or the present government. In the Philippines, for example, political dynasties comprise over 70% of its Congress. The impact of political dynasties on socioeconomic outcomes such as poverty is however an empirical question. Do political dynasties exacerbate poverty? This paper presents evidence of the impact of political dynasties on poverty. The analysis of data from the Philippines finds a positive effect of political dynasties on poverty outside of Luzon.